Exonuclease III-Regulated Target Cyclic Amplification-Based Single Nucleotide Polymorphism Detection Using Ultrathin Ternary Chalcogenide Nanosheets - Hu, Yanling; Tan, Chaoliang; Lin, Xin; Lai, Zhuangchai; Zhang, Xiao; Lu, Qipeng; Feng, Ning; Yang, Dongliang; Weng, Lixing (Frontiers in Chemistry, 2019)
For the first time, we report that the ternary chalcogenide nanosheet exhibits different affinity towards oligonucleotides with different lengths and efficiently quenches the fluorescence of dye labeled DNA probes. Based on these findings, as a proof-of-concept application, the ternary chalcogenide nanosheet is used as a target cyclic amplification biosensor, showing high specificity in discriminating single-base mismatch. This simple strategy is fast and sensitive for the single nucleotide polymorphism (SNP) detection. Ultralow detection limit of unlabeled target (250 fM) and high discrimination ratio (5%) in the mixture of perfect match (mutant-type) and single-base mismatch (wild-type) target are achieved. This sensing method is extensively compatible for the SNP detection in clinical samples, making it a promising tool for the mutation-based clinical diagnostic and genomic research.